Relationship between the Big Five Personality Traits and Social Adjustment among Undergraduate Students in a Public University - Okoth, Komolo Joshua (JOOUST, 2023)
The current cohort of undergraduate students is encountering a period of change that is marked by uncertainty, undisciplined behaviour, and stress. These factors have presented obstacles to their social adaptation as they engage in behaviours which include alcohol and drug abuse, suicidal tendencies, dating, violence and unplanned pregnancies. Kenyan universities have put in place various measures such as, comprehensive orientation programmes for students, academic advisory programmes, counseling services, health services, and chaplaincy. However, the problem of social maladjustment persists among undergraduate students. This study, therefore aimed to explore the relationship between the big five personality traits and social adjustment among undergraduate students. The study had the following objectives: to establish the relationship between extraversion and social adjustment of undergraduate students; to find out the relationship between agreeableness and social adjustment of undergraduate students; to establish the relationship between conscientiousness and social adjustment of undergraduate students; to investigate the relationship between neuroticism and social adjustment of undergraduate students; and to examine the relationship between openness and social adjustment of undergraduate university students. The research was informed by Goldberg's theory of the big five personality traits, and a concurrent triangulation design within a mixed method approach was employed. The target population consisted of 4805 undergraduate students and 5 university staffs, making a total population of 4810. The sample size included 756 students, one Dean of students, one Career counselor, one student Counselor, one Catering and accommodation officer, and one sports and games officer, thus a total sample size of 761. Simple random sampling and purposive sampling techniques were utilized. The quantitative data was collected using an Integrated Student Questionnaire (ISQ), while qualitative data was obtained through an interview schedule with a student counselor, a catering and accommodation officer, and a career counselor. The content validity of the research instruments was ensured through the expert judgment of university supervisors, while the internal validity of the constructs was confirmed using the Kaiser-Meyer-Oklin measure of sampling adequacy (KMO Index) and Bartlett's Test of Sphericity. The reliability of the questionnaires was verified using Cronbach's alpha values ranging from 0.630 to 0.684. The quantitative analyses utilized descriptive and inferential statistics, while the qualitative data were analyzed through thematic analysis. The findings showed that well-adjusted students tend to exhibit high levels of discipline, academic achievement, and self-responsibility. Certain personality traits are associated with better and faster social adjustment, particularly extraversion, agreeableness, conscientiousness, and openness. Certain personality traits have a higher completion rate in university due to their higher levels of positive social adjustment, particularly extraversion, agreeableness, conscientiousness, and openness. Students' social adjustment varies with each personality trait type. Openness to experience personality type had the most significant impact on students' social adjustment, while extraversion and neuroticism had the least impact on students' social adjustment, respectively. Educators can use the findings to recognize and accommodate the individual differences of their students. The dean of students can also develop measures to support proper student adjustment to college and mitigate any challenges associated with it. Ministry of education and university administrators can utilize the findings to design effective policies and programs that enhance student adjustment and reduce cases of indiscipline resulting from maladjustment. Parents and guardians can benefit from the study's findings by preparing their children for the psychosocial challenges they may encounter at the university. The findings can be applied to other contexts or serve as a basis for future research.
Keywords: Relationship between the Big Five Personality Traits and Social Adjustment among Undergraduate Students in a Public University